2021
DOI: 10.3390/ijerph18105232
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Implant Behavior of Tissue Level Dental Implants with a Convergent Neck

Abstract: Introduction: The aim of this retrospective study was to analyze the radiographic peri-implant bone loss of bone level implants and tissue level implants with a convergent neck in screw-retained single crowns and in screw-retained fixed partial prostheses, after two years of functional loading. Materials and methods: The sample was divided into two groups according to their type: Group I: supracrestal implants with convergent transmucosal neck; Group II: crestal implants. In each group we distinguish two subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Therefore, implants at premolar sites may lead to PI more frequently than do those at molar areas. Similarly, in other studies of implant type, tissue‐level implants have caused less bone loss than have bone‐level implants 32,33 . However, split‐mouth research indicated that tissue‐ and bone‐level implants have similar clinical and radiographic outcomes among patients who have a history of periodontitis 34 .…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, implants at premolar sites may lead to PI more frequently than do those at molar areas. Similarly, in other studies of implant type, tissue‐level implants have caused less bone loss than have bone‐level implants 32,33 . However, split‐mouth research indicated that tissue‐ and bone‐level implants have similar clinical and radiographic outcomes among patients who have a history of periodontitis 34 .…”
Section: Discussionmentioning
confidence: 81%
“…It is important to note that neck design was statistically significant. Similarly, Agustín et al (2021) [ 23 ] placed a total of 120 implants divided into two groups. The first group was composed of implants with convergent transepithelial tissue-level collars, and the second group were bone-level implants, among which significant differences were found regarding peri-implant bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, periapical radiography offers the lowest exposure dose compared to other modalities. 26 Thus, we assessed differences in crestal bone levels after oneyear of follow-up using standardized periapical radiographs. A long cone paralleling technique and a customized radiographic stent were used to standardize the x-ray incidence method.…”
Section: Suppurationmentioning
confidence: 99%
“…This stent was saved for later visits to allow standardized film placement and cone angulation throughout the follow-up period. 13,26 In order to have accurate results, it is mandatory to start with the determination of definite reference points on implant surfaces.…”
Section: Suppurationmentioning
confidence: 99%
See 1 more Smart Citation